A Modular Track and Signaling Simulation Trainer for Railway Technology Program - Dumalag, Alexi Maxine A.; Jatulan, Mark Joseph A.; Marmol, Marlon P.; Taneo, Abegail A.; Sison, Ghazali Illuminada R.; Garcia, Julius G.; Bunag, Sherlie D.; Ballesteros, Mariezol V.; Delizo, Carlo Jay G. (IC-ITECHS, 2024)
The modular railway track and signaling simulation trainer research project was developed to provide an enjoyable and educational tool to train railway students and professionals upon recognizing the need for effective training in traffic and signaling safety-critical areas. It provides a miniature model that accurately replicates railway switch points and signaling systems with modules depicting track layouts and signaling conditions created using Programmable Logic Controller (PLC) and Human-Machine Interface (HMI). The prototype's accurate and efficient miniature railway model showed that the simulation trainer was very effective. The survey demonstrated that railway students and professionals were satisfied with the trainer's performance and various use and educational potential for students. This simulation trainer design successfully changes railway training programs because it offers a relatively safe and exciting environment that allows learners to get practical experience and understanding of railway operations. The modular design of the trainer will facilitate future expansion and customization, making it adaptable to railway training needs and technology. The simulation trainer should include level crossings, track circuits, and train detection systems for further investigation. This would provide an improvement in the comprehensiveness and flexibility of the trainer, therefore helping with providing skilled railway workers.